(untitled) (Medical Forum Monthly, 2024)
Objective: To know the frequency of bronchogenic carcinoma in smoker patients presenting with hemoptysis using fiberoptic bronchoscopy technique Study Design: Description case series study Place and duration: This study was carried out at the pulmonology unit of Postgraduate Medical Institute Lady Reading Hospital Peshawar, KPK from 18/09/2007 to 18/09/2008. Material and Methods: Two hundred and fifty smoker patients presenting with hemoptysis, having clinical suspicion of bronchogenic carcinoma and fulfilling the inclusions criteria underwent fiberoptic bronchoscopy. The bronchoscopic findings and other demographic information were determined regarding their frequencies and percentage. Results: Fifty Nine point Two Percent (59.2%) patients were found to have pulmonary tuberculosis, seventeen Point Two Percent (17.2%) were diagnosed to have bronchiectasis, 11.6% chronic bronchitis, 5.2% with bronchogenic carcinoma and 6.8% remained with undetermined cause. Conclusion: Pulmonary Tuberculosis is a major cause of hemoptysis in relatively younger smokers but the bronchogenic carcinoma is a major cause of hemoptysis in smokers of old age group.